Efek Residu Media Tanam dengan Penambahan Kompos Secara Berulang Terhadap Pertumbuhan dan Serapan Hara Nitrogen Tanaman Kailan - Sholihah, Anis; Sugianto, Agus (Universitas Islam Malang, 2022)
This study aims to determine the potential of planting media residues from rice crop residues in the second planting period which were given input of a mixture of kiapu compost and straw with various compositions with the indicator plant used was kailan which belongs to the potential vegetable group and has a fairly high nutritional value. The study used a randomized block design with treatments consisting of 5 compost mixtures and 2 comparison treatments, namely pearl NPK fertilizer treatment and control so the treatment was as follows; M0 : control, M1 : 100% kiapu, M2 : 75% kiapu + 25% rice straw, M3 : 50% kiapu + 50% rice straw, M4 : 25% kiapu + 75% rice straw, M5 : 100% straw and M6 : NPK. The results showed that repeated application of the compost mixture was able to give a positive residual effect so that it could increase growth, yield and N uptake in kailan plants. The increase in plant length due to the addition of repeated compost ranged from 1.96% to 22.79%, leaf area ranged from 11.28% to 75.63% and total plant fresh weight ranged from 28.85% to 59.94%. The treatment with compost significantly increased root N uptake, canopy N uptake and total N uptake compared to control, ranging from 223.67% to 283.36% at root N uptake, 175.03% to 232.47% at canopy N uptake and 194, 43% to 241.63% on the total N uptake of plants.